A study of strategic responses and actions of Malaysian law firms in face of the liberalisation of legal services in Malaysia - Cheah, Soo Chuan (2013)
Malaysia is set to embrace the liberalisation of legal services. This will pose strategic challenges to Malaysian law firms and will impact on industry competition. It is not certain as to how Malaysian law firms perceive the liberalisation of legal services, and what strategic actions will be taken by them in order to maintain their strategic position and competitiveness. Against this backdrop, this study seeks to find out the answers to the questions as to how Malaysian law firms perceive the liberalisation of legal services – whether it is perceived as a threat or an opportunity; the strengths, weaknesses and core competencies of Malaysian law firms in face of the liberalisation of legal services; and the strategic actions taken by Malaysian law firms in order to maintain their strategic position and competitiveness. The bodies of literature that were used to inform this research are the conceptual framework of Porter’s five forces and the theory of the resource-based view. Using qualitative approach, this research seeks to examine the research problem by interviewing participants who are partners of Malaysian law firms as well as a representative from the professional body which represent the largest State Bar Committee in Malaysia, i.e. the Kuala Lumpur Bar Committee. From the fieldwork, it was found out that Malaysian law firms generally perceive the liberalisation of legal services as both a threat and an opportunity. It was also found out that Malaysian law firms do have their own strengths, weaknesses and core competencies in face of the challenges that arise from the liberalisation of legal services. This research confirmed and prove the usefulness of Porter’s five forces framework to assess the attractiveness of the legal industry in Malaysia based on the strengths of five competitive forces and the resource-based view to analyse the internal asset (i.e. resources, capabilities and competencies) of Malaysian law firms. Future research may be built upon this research to study the impacts of the liberalisation of legal services on Malaysian law firms.